Assessing nutritional status of newborns by Metcoff’s method - García Alberca, Marita Isenia (2019)
Introduction: Despite anthropometric parameters (weight, length and head circumference) used in the nutritional evaluation of newborn can be normal; nevertheless, some newborns delivered at term catalogued like appropiate for gestational age (AGA), suffer from fetal malnutrition (FM) when the compartments are valued greasy and protein through Metcoff’s test. Objective: the incidence of FM in term newborns AGA, using clinical assessment of nutritional status at birth and its qualification according to Metcoff, from December 2011 - January 2012 in Hospital of Sullana. Materials and Methods: A prospective, cross-sectional, descriptive, and mm study was made in the Hospital de Sullana. The nutritional state was evaluated of a sample of 93 newborns delivered at term AGA, alive, eutocic and singleton delivery, without the presence of risk factors that affect the health of the mother, the newborn or both. The selection was of probabilistic sample of type accidental. Results are shown in tables and graphs. Results: 93 newborns delivered at term AGA were evaluated. There was predominance of male sex (50.5 %) with respect to the female sex (49.5 %). The mean values and standard deviations of the weight, length, head circumference and circumference for the considered ones as nourished well were as follows: 3282.2 ± 325.3 g, 49.12 ± 1.54 cm, 33.67 ± 1.23 y 10.36 ± 0.67cm, respectively, whereas for the undernourished ones were 2972.7 ± 268.2 g, 48.7 ± 2.01 cm, 33.03 ± 1.34 cm y 9.71 ± 0.68. Conclusion: Metcoff’s test showed clinical fetal malnutrition in 15 term newborns AGA, which represents an incidence of 16 %.